PENGARUH KATALOG PRODUK TERHADAP MINAT BELI KEMBALI KONSUMEN CARREFOUR YOGYAKARTA - Firman Cahyadi (Jurnal Riset Manajemen dan Bisnis, 2011)
ABSTRACT The research aims to analyze whether the advertised product, the advertisement design, the advertisement message, the brand image and the price of the advertised has significant influence toward the re-purchase interest of the Carrefour Plaza Ambarrukmo Yogyakarta customers. The results show that the advertised product, the advertisement design, the advertisement message, the brand image and the price of the promoted products have significant and positive influence toward the repurchase interest. The result of the research also indicates that price is the most dominant factor in influencing the re-purchase interest. Keywords: product, advertisement, brand, price, re-purchase